Mathematical Problem Solving Ability: The Impact of Auditory, Intellectually and Repetition Learning Models and Bassed Learning Problems on Trigonometry Materials - Hartati, Suci; Gufron, Dadang; Melinda, Rita (Universitas Islam Negeri Raden Intan Lampung, 2020)
Mathematical problem-solving ability is one thing that must be possessed by students in learning mathematics. This study aims to determine students' problem solving abilities with auditory, intellectual and repetition (AIR) and problem bassed learning (PBL) learning models in mathematics learning. This research is a quasy experimental study consisting of two independent variables namely the learning model AIR and PBL and the dependent variable namely problem solving. The results of the T test hypothesis indicate that the AIR model has a different impact / influence in influencing students' mathematical problem solving abilities compared to the PBL model. In the test of students 'mathematical problem solving abilities obtained AIR models are better at influencing students' mathematical problem solving abilities compared to PBL models.